KAJIAN LINGUISTIK ANTROPOLOGIS PENAMAAN KAPAL NELAYAN DI TEGALKAMULYAN, CILACAP - Hariyanto, Prima; Suyuti, Muhammad Wildan; Kristianti, Yuliana; Rahma, Nurul Na’imahtul; Amanda G.P., Safira Rizky (ETNOLINGUAL, 2025)
Abstract: This research aims to analyze the naming of fishing boats in Tegalkamulyan, Cilacap, Central Java, Indonesia, using an anthropological linguistic approach. The method used is qualitative with data collection techniques through participant observation, in-depth interviews, and analysis of documents obtained from HNSI. The research results show that the names of fishing boats in Tegalkamulyan have various forms, meanings and functions. The names are also in various languages. This research also shows that the naming of fishing boats in Tegalkamulyan is closely related to the culture and traditions of the local fishing community. The meaning of naming fishing boats in Tegalkamulyan is in the form of hope, event marker, cultural identity and origin. The naming functions found include identification, legal regulations, security and safety, operations and logistics, as well as promotion and marketing. Keywords: boat naming, fishermen, anthropological linguistics, meaning, Cilacap